PROFILE OF WOMEN WHO ATTEND FITNESS CENTERS IN THE CITY OF DIVINO-MG (Fiep Bulletin - online, 2013)
The understanding of the perception of women regarding the fitness center market constitutes itself in pertinent instrument of orientation and analysis in order to allow expansion and improvements in this segment, as well as to identify and analyze the assumptions that have supported this process. The purpose of this research was to identify the profile of women who attend fitness centers in the City of Divino - MG. It was applied a not validated questionnaire to members of fitness centers of this city who were willing to participate of the study, who previously signed a term of informed consent. The sample consisted of 86 women. It was used a descriptive statistics of Microsoft Excel program in the data analysis. The study was approved by the Human Research Ethics Committees (HREC) at UFV, according the office number  OF.REF.098/2012/CEPH/wmt. This survey is part of the study "Profile of users and characteristics of fitness centers for women in the city of Divino - MG". In the current study it was analyzed the characteristics that constitute the users' profile, as well as the reasons that led them to attend fitness center and the reasons that led to their staying in these environments; it was also analyzed the satisfaction of individuals regarding professional services, reception and service, comfort and convenience, property facilitators, implicit services, physical infrastructure and devices and cost. It was verified that the results presented differ from previous studies, such as Lima and Maffia (2010), in the questions about the individuals goals in certain age groups.
Keywords: femaly fitness centers; sedentary lifestyle; physical activity.